La professionnalisation des enseignants du secondaire en France. Entre injonctions institutionnelles et approche sociologique - Aziz Jellab (Éducation et Socialisation)
In France, the development of the researches concerning the professionalization of the teachers testifies of the liveliness of this theme as its political and educational stakes. The institutional call to the professionalization takes place as the school in France, despite of several reforms, turns out to be very unequal. A tension persists nevertheless between an institutional normative look calling up to the professionalization of the teachers and a sociological approach, although attached to define the contextual and biographic professional conditions. And as the professional identity of the secondary school teachers is fundamentally associated with the school curricula, we can consider that their relation with knowledges offers the possibility of study their ordinary activities. Having presented the searches about a professionalization and two searches about the young teachers of the secondary sector and the professors in a vocational school, this text invites to think professional socialization as process of professionalization, by questioning the knowledges mobilized in the professional situations, the influence of the career on the educational choices, and the place of the hardship which remain constituent of professional activity.